2021
DOI: 10.1042/cs20200844
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-associated membranes (MAMs): a potential therapeutic target for treating Alzheimer’s disease

Abstract: Alzheimer's disease (AD), a progressive neurodegenerative disorder, is a leading global health concern for individuals and society. However, the potential mechanisms underlying the pathogenesis of AD have not yet been elucidated. Currently, the most widely acknowledged hypothesis is amyloid cascade owing to the brain characteristics of AD patients, including great quantities of extracellular β-amyloid (Aβ) plaques and intracellular neurofibrillary tangles (NFTs). Nevertheless, the amyloid cascade hypothesis ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 146 publications
0
32
0
Order By: Relevance
“…The mechanisms in the early phase leading to axonal damage in AD pathology remain unclear. MAM dysregulation is an early event in AD pathogenesis (for review, see Yu et al, 2021 ). Axonal BACE1 levels were increased in axonal swellings in an AD mouse model by genetic deletion of an adaptor protein GGA3, which regulates lysosomal degradation of BACE1, leading to increased production of Aβ ( Lomoio et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms in the early phase leading to axonal damage in AD pathology remain unclear. MAM dysregulation is an early event in AD pathogenesis (for review, see Yu et al, 2021 ). Axonal BACE1 levels were increased in axonal swellings in an AD mouse model by genetic deletion of an adaptor protein GGA3, which regulates lysosomal degradation of BACE1, leading to increased production of Aβ ( Lomoio et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Later on, Poston et al identified 1212 candidates, including weak soluble proteins at the MAM [21]. Until now, various proteins (approximately 1000) localized within the MAMs were identified in the brain and liver with the aid of in-depth mass spectrometry analysis [22]. Above all, the components within MAMs were highly conserved among species and tissues.…”
Section: The Structural Composition Of the Mitochondria-associated Membranes (Mams)mentioning
confidence: 99%
“…In fact, as previously mentioned, mitochondria have been shown to be a direct site for the accumulation of aggregated Aβ in the neurons of both animal models of AD and samples obtained from patients of the disease. One of the mechanisms that can explain the cytotoxicity of the peptide involves the mechanisms of the calcium transfer from ER to mitochondria, which has been demonstrated in various models of AD [ 142 , 143 , 144 , 145 ]. Specifically, Boyman et al showed that the content of the mitochondrial calcium uniporter (MCU), a structure that allows calcium to flow from the ER to mitochondria [ 146 ], significantly increases in fibroblasts obtained from AD patients, when compared with healthy age-matched individuals [ 147 ].…”
Section: Mitochondrial Calcium Homeostasismentioning
confidence: 99%
“…The interaction between mitochondria and ER in mammalian cells is mediated by the mitochondria-associated ER membranes (MAMs) [ 148 ]. MAMs play a crucial role not only in calcium homeostasis but also in the regulation of lipid synthesis, mitochondrial dynamics, energy metabolism, cell survival, and apoptotic signaling [ 142 , 145 ]. Interestingly, using mammalian cells, Area-Gomez et al demonstrated that in AD models there is an upregulation of MAM activity, which elevates the crosstalk between mitochondria and ER, deleteriously affecting mitochondrial calcium homeostasis [ 149 ].…”
Section: Mitochondrial Calcium Homeostasismentioning
confidence: 99%
See 1 more Smart Citation